Law Enforcement Against Traffic Violations In Traffic Units In The Jurisdiction Of The Deli Serdang City Resort Police - Sugiono; T. Riza Zarzani (International Journal of Society and Law, 2024)
The National Police of the Republic of Indonesia (Polri) is tasked with maintaining public security, law enforcement, and community service, including traffic law enforcement. The Traffic Unit (Satlantas) plays a pivotal role in ensuring traffic safety and order in its jurisdiction, as mandated by Law Number 22 of 2009 concerning Road Traffic and Transportation. However, traffic violations remain prevalent, with common offenses such as not wearing helmets, ignoring traffic signs, and lacking proper documentation. These violations disrupt traffic order and contribute to accidents. This study examines the authority and implementation of traffic law enforcement by the Deli Serdang Police Traffic Unit, focusing on the period 2022–2024. It also evaluates the effectiveness of enforcement efforts, considering challenges like restrictions on stationary enforcement (raids) and fluctuating compliance levels. Preventive measures, such as public education, and repressive actions, like ticket issuance, are analyzed. Findings highlight the need for a balanced approach that combines firm enforcement with humanistic service to enhance legal awareness and public trust. This research aims to provide insights into improving traffic law enforcement and fostering a culture of traffic discipline, contributing to public safety and economic development in Deli Serdang.